2014
DOI: 10.2147/ijn.s48136
|View full text |Cite
|
Sign up to set email alerts
|

Dendrosomal curcumin nanoformulation downregulates pluripotency genes via miR-145 activation in U87MG glioblastoma cells

Abstract: Glioblastoma is an invasive tumor of the central nervous system. Tumor recurrence resulting from ineffective current treatments, mainly due to the blood–brain barrier, highlights the need for innovative therapeutic alternatives. The recent availability of nanotechnology represents a novel targeted strategy in cancer therapy. Natural products have received considerable attention for cancer therapy because of general lower side effects. Curcumin is a new candidate for anticancer treatment, but its low bioavailab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 46 publications
4
24
0
Order By: Relevance
“…These vesicles, or polymersomes, can be made of one or more different high-molecular weight amphiphilic block copolymers such as oleic acid and PEG 400 as a diblock nanostructure. This combination has been shown effective in delivering curcumin and reducing tumor burden in mouse models [75, 76]. Monomethoxy PEG has a higher molecular weight of 2 kDa versus 400 Da and has also been tested in attempt to obtain a better thermodynamic profile [77].…”
Section: Delivery Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…These vesicles, or polymersomes, can be made of one or more different high-molecular weight amphiphilic block copolymers such as oleic acid and PEG 400 as a diblock nanostructure. This combination has been shown effective in delivering curcumin and reducing tumor burden in mouse models [75, 76]. Monomethoxy PEG has a higher molecular weight of 2 kDa versus 400 Da and has also been tested in attempt to obtain a better thermodynamic profile [77].…”
Section: Delivery Mechanismsmentioning
confidence: 99%
“…Dendrosome carriers, comprised of esterified oleoyl chloride and polyethylene glycol 400, have recently been published as effective means of delivery curcumin [75, 76]. In vitro data treating U87MG GBM cells with curcumin, dendrosomal curcumin, and empty dendrosome found that dendrosomal curcumin had superior efficacy at 24, 48, and 72 hours.…”
Section: Delivery Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tahmasebi Mirgani et al have reported curcumin nano-formulation based on dendrosomes (branchedpolymeric micelles) that can down-regulate pluripotency genes in U87MG glioblastoma cells [12]. Furthermore, Erfani et al [13] have revealed that diblock copolymer-based micelles can be considered for delivery of curcumin molecules to the cancer cells [13].…”
Section: Gsmentioning
confidence: 99%
“…This is mainly due to its low aqueous solubility, poor absorption, low bioavailability, extensive metabolism and rapid elimination [5,6,8,9].The employment of nano-drug delivery systems has allured the attention of many researchers to conquer the physiochemical limitations of curcumin [10]. Lipid-based and polymer-based nanocarriers are among the most favoured nano-systems approved as carriers of anti-cancer drugs to be implemented in clinical trials [6,11].Tahmasebi Mirgani et al have reported curcumin nano-formulation based on dendrosomes (branchedpolymeric micelles) that can down-regulate pluripotency genes in U87MG glioblastoma cells [12]. Furthermore, Erfani et al [13] have revealed that diblock copolymer-based micelles can be considered for delivery of curcumin molecules to the cancer cells [13].Here, an mPEG urethane gemini surfactant was synthesised and its viability as a curcumin delivery vehicle was examined.…”
mentioning
confidence: 99%